Объяснение:
1)
а)
б)
2)
3)
4)
выражаем х и z через первые два выражения:
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
1)
а)![\frac{ {y}^{2} + 4y}{ {y}^{2} } = \frac{y(y + 4)}{ {y}^{2} } = \frac{(y + 4)}{y} \frac{ {y}^{2} + 4y}{ {y}^{2} } = \frac{y(y + 4)}{ {y}^{2} } = \frac{(y + 4)}{y}](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20%7By%7D%5E%7B2%7D%20%20%2B%204y%7D%7B%20%7By%7D%5E%7B2%7D%20%7D%20%20%3D%20%20%5Cfrac%7By%28y%20%2B%204%29%7D%7B%20%7By%7D%5E%7B2%7D%20%7D%20%3D%20%20%5Cfrac%7B%28y%20%2B%204%29%7D%7By%7D%20%20)
б)
2)
а)
б)
3)
4)
выражаем х и z через первые два выражения: